Niosome‐encapsulated tobramycin reduced antibiotic resistance and enhanced antibacterial activity against multidrug‐resistant clinical strains of Pseudomonas aeruginosa. Issue 6 (31st August 2020) - Hedayati Ch, Mojtaba; Abolhassani Targhi, Arefeh; Shamsi, Farzaneh; Heidari, Fatemeh; Salehi Moghadam, Zahra; Mirzaie, Amir; Behdad, Reyhaneh; Moghtaderi, Maryam; Akbarzadeh, Iman
Abstract: In the current study, niosome‐encapsulated tobramycin based on Span 60 and Tween 60 was synthesized and its biological efficacies including anti‐bacterial, anti‐efflux, and anti‐biofilm activities were investigated against multidrug resistant (MDR) clinical strains of Pseudomonas aeruginosa. The niosomal formulations were characterized using scanning electron microscopy, transmission electron microscopy, and dynamic light scattering measurement. The encapsulation efficiency was found to be 69.54% ±; 0.67. The prepared niosomal formulations had a high storage stability to 60 days with small changes in size and drug entrapment, which indicates that it is a suitable candidate for pharmaceutical applications. The results of biological study showed the anti‐bacterial activity via reduction of antibiotic resistance, enhanced anti‐efflux and anti‐biofilm activities by more folds in comparison to free tobramycin. In addition, niosome encapsulated tobramycin down‐regulated the MexAB‐OprM efflux genes, pslA and pelA biofilm related genes in MDR P. aeruginosa strains. The anti‐proliferative activity of formulation was evaluated against HEK293 cell lines, which exhibited negligible cytotoxicity against HEK293 cells. The finding of our study shows that encapsulation of tobramycin in niosome enhanced the antibacterial activity and reduced antibiotic resistance in MDR strains of P. aeruginosa comparing to free tobramycin and it can be considered as a favorable drug delivery system.